2021
DOI: 10.1080/2330443x.2021.1919260
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Matching for Observational Studies That Integrate Quantitative and Qualitative Research

Abstract: A quantitative study of treatment effects may form many matched pairs of a treated subject and an untreated control who look similar in terms of covariates measured prior to treatment. When treatments are not randomly assigned, one inevitable concern is that individuals who look similar in measured covariates may be dissimilar in unmeasured covariates. Another concern is that quantitative measures may be misinterpreted by investigators in the absence of context that is not recorded in quantitative data. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Further, the units within a matched group can be far from each other in covariate space -i.e., the matched groups are generally not auditable [Parikh et al, 2022b]. To date, the only observational causal inference techniques that attempt to optimize accuracy while maintaining auditability are those stemming from the almost-matchingexactly (AME) framework, namely optimal matching (optMatch) [Yu et al, 2021, Kallus, 2017, genetic matching (GenMatch) [Diamond and Sekhon, 2013], FLAME/DAME [Wang et al, 2017, Dieng et al, 2019, MALTS [Parikh et al, 2022b[Parikh et al, , 2019[Parikh et al, , 2022a and AHB [Morucci et al, 2020] algorithms. FLAME/DAME can scale to extremely large datasets but handles only categorical variables.…”
Section: Background and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the units within a matched group can be far from each other in covariate space -i.e., the matched groups are generally not auditable [Parikh et al, 2022b]. To date, the only observational causal inference techniques that attempt to optimize accuracy while maintaining auditability are those stemming from the almost-matchingexactly (AME) framework, namely optimal matching (optMatch) [Yu et al, 2021, Kallus, 2017, genetic matching (GenMatch) [Diamond and Sekhon, 2013], FLAME/DAME [Wang et al, 2017, Dieng et al, 2019, MALTS [Parikh et al, 2022b[Parikh et al, , 2019[Parikh et al, , 2022a and AHB [Morucci et al, 2020] algorithms. FLAME/DAME can scale to extremely large datasets but handles only categorical variables.…”
Section: Background and Assumptionsmentioning
confidence: 99%
“…Auditability allows domain experts to validate the estimation procedure, argue about the violation of key assumptions, and determine whether the analysis is trustworthy. Parikh et al [2022a] and Yu et al [2021] showed that the audit of matched groups using external unstructured data is crucial in high-stakes healthcare and social science scenarios. Since causal analyses often depend on untestable assumptions, it is critical to determine whether all important confounders are accounted for, if data are processed correctly, and whether the treatment and control units in the matched groups are cohesive enough to be comparable [Parikh et al, 2022c].…”
Section: Introductionmentioning
confidence: 99%